Analisis Kebutuhan Penggunaan PopUp Book Bilingual dalam Meningkatkan Literasi Sains dan Bahasa Inggris SD - Muzakki, Muhammad Alie; putri, aprilia riyana (Tunas Nusantara, 2024)
Science education at the elementary level often faces challenges, especially in abstract topics such as magnetism, electricity, and technology. This study aims to analyze the need for the use of a bilingual PopUp Book in improving elementary students’ science literacy and English proficiency. The study used a qualitative descriptive method with a survey approach, involving 4 teachers and 40 students from four elementary schools in Jepara Regency. Data collection instruments included questionnaires and interviews, which were analyzed descriptively. The results showed that 70% of students had difficulty understanding science topics, and 80% of students expressed a strong interest in using interactive PopUp Books. Additionally, 75% of teachers supported the use of bilingual media to enhance science and English literacy. However, challenges related to students' varying English proficiency levels were identified. In conclusion, the bilingual PopUp Book has great potential to improve elementary students' science and English literacy, provided that teachers receive adequate training and language usage is adjusted to the students' proficiency